SYAKHSIYAH DALAM HUKUM ISLAM - Chalid, Anna Rahmah (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
This paper seeks to discuss syakhsiyah according to Islamic law. The discussion paper seeks to conduct a comparison of some legal systems that talk about syakhsiyah or legal subjects. Therefore, the discussion is expected to provide an understanding of how the legal subject or syakhsiyah setting in some source of law, particularly in the Islamic Sharia. With the affirmation of syakhsiyah in Islamic Law, will greatly impact the lives of Muslims in their dealings with other human beings, because the settings are clear and obvious rights and obligations to be performed by a person against another person.